2019
DOI: 10.5187/jast.2019.61.3.147
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different parities on reproductive performance, birth intervals, and tail behavior in sows

Abstract: A goal for swine farming is the improvement in the number of live-born and weaned piglets per sow. Hence, the effect of parities should consider the correlation between the component traits of reproductive performance, weaning, and duration. Sows were housed in farrowing pens (W 2.2 × D 1.8 × H 1.2 m) on a partially slatted plastic floor. Twenty sows used in this study were between the first and sixth parity in gilts (P1), parity 2–5 (P3), and parity 6–9 (P6). Data collection by parity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
3
8
0
Order By: Relevance
“…On the other hand, van Dijk et al [ 28 ] demonstrated that parity number did not affect the duration of the expulsive stage. Additionally, Yang et al [ 29 ] found a shorter farrowing duration in sows with higher parity numbers (6–9) compared to sows with lower parity numbers (i.e., 1 and 2–5). However, in their study, sows with parity numbers 6–9 had a smaller total number of piglets born per litter (12.4 ± 3.2) than sows with parity numbers 2–5 and 1 (15.5 ± 3.1 and 16.8 ± 1.8) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, van Dijk et al [ 28 ] demonstrated that parity number did not affect the duration of the expulsive stage. Additionally, Yang et al [ 29 ] found a shorter farrowing duration in sows with higher parity numbers (6–9) compared to sows with lower parity numbers (i.e., 1 and 2–5). However, in their study, sows with parity numbers 6–9 had a smaller total number of piglets born per litter (12.4 ± 3.2) than sows with parity numbers 2–5 and 1 (15.5 ± 3.1 and 16.8 ± 1.8) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Yang et al [ 29 ] found a shorter farrowing duration in sows with higher parity numbers (6–9) compared to sows with lower parity numbers (i.e., 1 and 2–5). However, in their study, sows with parity numbers 6–9 had a smaller total number of piglets born per litter (12.4 ± 3.2) than sows with parity numbers 2–5 and 1 (15.5 ± 3.1 and 16.8 ± 1.8) [ 29 ]. Litter size is positively correlated with farrowing duration, and thus, in sows with large litters, farrowing may last longer.…”
Section: Discussionmentioning
confidence: 99%
“…The age and weight at first mating are considered as critical factors for a greater litter size in gilts lifetime production [1,2]. Decades of selection for improved litter size, changes the physiological response of gilts to management or environmental factors [3]. There is a large variation in herd gilts replacement, as almost half the sows are culled every year and their lifetime litter size is only between 30 and 40 piglets [4].…”
Section: Introductionmentioning
confidence: 99%
“…Among the main factors that influence sow fertility are weather [72], housing conditions [73], nutritional status [72], duration of gestation [74], endocrine activity [72], and sow lifetime productivity [75]. In the present study, four maternal crosses were considered because maternal ability can influence phenotypic performance in species with numerous litters, such as pigs [76][77][78]. In the case of boars, two racial groups were used because of the selection objective in terminal crossings [79][80][81].…”
Section: Discussionmentioning
confidence: 99%